Family or Freedom : People of Color in the Antebellum South - West, Emily (Book collections on Project MUSE., 2012)
In the antebellum South, the presence of free people of color was problematic to the white population. Not only were they possible assistants to enslaved people and potential members of the labor force; their very existence undermined popular justifications for slavery. It is no surprise that, by the end of the Civil War, nine Southern states had enacted legal provisions for the ""voluntary"" enslavement of free blacks. What is surprising to modern sensibilities and perplexing to scholars is that some individuals did petition to rescind their freedom. Family or Freedom investigates th.